Chance-Constrained Linear Programming with Chi-Square Type Deviates - Sengupta, Jati K. (Management Science, 1972)
The implications of replacing the assumption of normal distribution of the parameters (A, b, c) by chi-square and other related nonnegative distributions are discussed here in the framework of chance-constrained linear programming.